Prionoid Proteins in the Pathogenesis of Neurodegenerative Diseases - Wells, Cameron; Brennan, Samuel E.; Keon, Matt; Saksena, Nitin K. (Frontiers in Molecular Neuroscience, 2019)
There is a growing body of evidence that prionoid protein behaviors are a core element of neurodegenerative diseases (NDs) that afflict humans. Common elements in pathogenesis, pathological effects and protein-level behaviors exist between Alzheimer’s Disease (AD), Parkinson’s Disease (PD), Huntington’s Disease (HD) and Amyotrophic Lateral Sclerosis (ALS). These extend beyond the affected neurons to glial cells and processes. This results in a complicated system of disease progression, which often takes advantage of protective processes to promote the propagation of pathological protein aggregates. This review article provides a current snapshot of knowledge on these proteins and their intrinsic role in the pathogenesis and disease progression seen across NDs.